AN ANALYSIS OF SECTORAL ALLOCATION IN UNION BUDGET AND ITS IMPACT ON STOCK MARKET PERFORMANCE (International Journal of Food and Nutritional Sciences, 2023)
This study analyses the Sectoral allocation in the Union Budget of India and its impact on stock market performance. The Union Budget is a key policy document that outlines the government’s priorities, including sectoral investments and financial allocations, influencing both economic growth and investor sentiment. Descriptive research has adopted to carry out this study. Researcher has selected 100 respondents as a sample size, and convenience technique has employed for the study. This study is based on primary data, researcher collected data from the respondents by structured close ended questionnaire with the help of survey technique. And also data extracted through secondary sources such as books, websites, journals, articles and many more. The study employed tables and charts for classification of the collected data, percentage and frequencies used for the analysis of collected data. The research aims to analyze how changes in budgetary allocations to various sectors, such as infrastructure, agriculture, technology, and healthcare, affect stock market performance, particularly stock prices and market indices. Preliminary findings indicates that sectors such as infrastructure, technology, and green energy tend to experience positive stock market reactions following budgetary allocations, as increased funding in these areas signals growth and investment opportunities. Conversely, sectors receiving reduced allocations or no focus may witness negative or neutral market responses. The research also highlights the role of investor expectations, market speculation, and fiscal policy in shaping market behavior.